Analysis of the Factors Affecting the Distribution of Banking Working Capital Loans in Central Kalimantan Province - Rahayu Sri Ningsih Panjaitan (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2021)
The purpose of this study is to determine: (1). The influence of interest rates on the distribution of working capital loans to banks in Central Kalimantan Province, (2). The influence of inflation on the distribution of working capital loans to banks in Central Kalimantan Province, (3). The influence of economic growth on the distribution of working capital loans to banks in Central Kalimantan Province. This study uses quantitative methods. The type of data used is secondary data obtained from the Central Statistics Agency and Bank Indonesia. And the analysis technique using multiple linear regression. The results of the analysis show that the interest rate, inflation and economic growth variables partially have no influence on working capital loans, inflation has no influence effect on working capital loans and economic growth has a positive and significant influence on working capital loans in Central Kalimantan Province. Simultaneously Interest rate variables (X1), inflation (X2) and economic growth (X3) have a significant influence on the distribution of working capital loans to banks in Central Kalimantan Province.